Dietary Factors in Relation to Helicobacter pylori Infection - Seyyed Ali Mard; Hossein Khadem Haghighian; Vahid Sebghatulahi; Bijan Ahmadi (Gastroenterology Research and Practice)
Background and Aim. Helicobacter pylori (HP) and diet are both risk factors for gastric cancer. The aim of this study was to evaluate the Helicobacter pylori infection and dietary habits common in Khuzestan province. Methods. This cross-sectional study was conducted in 2011–2013 on 374 patients. Participants were interviewed using a food frequency questionnaire and tissue sample of the antrum was sent for pathology lab. The histopathological major variables were graded on a scale of 3 (mild, moderate, and severe) and data analyzed using nonparametric tests. Results. In this study, of 160 patients (43%) that were determined, 8.1 percent had severe contamination. Among dietary patterns, relationship between energy intake and carbohydrate with H. pylori was significant. A direct association was found between mean daily intakes of sausage (P=0.001) and burgers (P<0.05) with HP infection. Low intake of fresh vegetables and fruits was the most significant risk factors (P<0.05). Conclusion. There is a possibility that some dietary factors such as consumption of fast foods and low intake of fresh vegetables may increase the chance of HP and severity of this infection.